Pilares Institucionais como determinantes das práticas Ambientais, Sociais e de Governança no Brasil e na Espanha - Villalba, Veronica Ahimaras (2023)
This study seeks to understand how Institutional Pillars influence Environmental, Social and Corporate Governance (ESG) sustainability practices in 20 publicly traded companies in Brazil and Spain. The research provides empirical evidence on organizational sustainability in specific contexts. The comparison of ESG practices between Brazil and Spain identifies areas of convergence and divergence, generating relevant information for sustainability policies and corporate strategies. The study contributes to Institutional Theory, highlighting the interdependence and intertwining of institutional pillars in ESG practices. As methodology, a documentary approach of an explanatory nature was used. Using Content Analysis, 37 reports published in 2022, in both countries, were analyzed, categories were created based on authors and reference guidelines. Next, we analyzed how the Institutional Pillars (Regulatory, Normative and Cultural-Cognitive) shape ESG strategies adopted in the two economies. In the Environmental dimension, Brazilian companies focus on preserving nature, while Spanish companies focus on reducing greenhouse gas emissions, in accordance with European Union regulations. The Regulatory Pillar plays a central role, with Brazil protecting critical areas, such as the Amazon, and Spain following guidelines from international agreements. In the Social dimension, Brazilian companies invest in community and equality, due to their collectivist society and high levels of inequality. In contrast, Spanish companies prioritize health and wellbeing, reflecting the country's socioeconomic context. Spain's Cultural-Cognitive Pillar promotes the inclusion strategies for marginalized groups. In Brazil, LGBTQIA+ inclusion becomes a socially accepted value and incorporated into organizational, governmental and social practices and structures. In the context of Corporate Governance, Brazilian companies focus on behavior and board composition, emphasizing anti-corruption policies. Historical corruption and the negative perception associated with it have created an institutional environment marked by a demand for greater transparency and integrity. The Spanish companies prioritize risk supervision and stakeholder involvement. The quality of governance is influenced by regulations that protect the rights of the parties involved, revealing the institutional stability of the European Union. The study advanced in relation to previous works by contributing with a more comprehensive and in-depth view of ESG practices, as well as knowledge about the interaction between the Environmental, Social and Corporate Governance dimensions, in a simultaneous and interconnected way. These advances have the potential todrive more effective sustainable policies and practices, both at the level of organizations and governments.